(untitled) (Estudos em Design, 2024)
Editores Cristina Portugal Rita Couto Avaliadores desta edição v. 32, n. 3 (2024) Adriana Gralow Adriana Miranda Adriana Sampaio Leite Alexandre Oliveira Aline Savi Álvaro Sousa Ana Berwanger Ana Pazmino André Ribeiro de Oliveira Antonio Colchete Filho Artur Mottin Beany Monteiro Carlo Franzato Cassia Carrara Domiciano Cassia Furtado Cayley Guimaraes Clice Mazzilli Cristiane Aun Bertoldi Chrystianne Ivanóski Cyntia Malaguti de Sousa Daniel Portugal Daniel Raposo Daniela Estaregue Alves Debora Buonano Deborah Christo Doris Kosminsky Edson Rufino[ Elisa Strobel do Nascimento Elizabeth Romani Fátima Waechter Finizola Filipe Campelo Xavier da Costa Frederico Braida Gabriel Patrocinio Gabriela Perry Gustavo Curcio Igor Ramos Ione Bentz Karina Porto Bontempo Kátia Carvalhaes Pêgo Laura Martins Lauren Arrussul Carús Luiz Agner Luiza Falcão Soares Cunha Madalena Grimaldi Marcelina Almeida Marina Carneiro Marcio Guimarães Marcos Braga Maria Do Carmo Gonçalves Curtis Maria Teresa Lopes Mariano Lopes de Andrade Neto Maurício Klafke Dick Olavo Neto Patrícia dos Santos Paulo Cesar Ferroli Rafaela Sarinho Raimundo Diniz Ravi Passos Renata Wanderley Rosane Martins Sandra Maria Souza Sérgio Luciano da Silva Silvia Schnaider Suzana Martins Tiago Silva Tomás Barata Walter Correia Walter Neto Verônica Freire Viviane Nunes